(untitled) (Research, Society and Development, 2021)
The article seeks to present bibliographic researches that make relation between the cognitive evaluation in elderly people and the possible damages caused by the Malaria at the Amazonas state. The objective of this research is to obtain data that can direct the psychological evaluation to the third age. To the data getting, it was searched information about the human development and the malaria infection, through books and scientific articles. It was searched instruments used in the psychological evaluation to collect data about cognitive abilities and executive functions; it was considered the theoretical reference of Papalia, D. E, Olds. S. W, & Feldman, R D (2006) Human development and Charchat-Fichman, Helenice et al. Decline of cognitive abilities during aging (2005). By the found results it was possible to perceive that the psychological evaluation lacks more researches in the theme, cognition and malaria. It was concluded that new studies may lead to more psychometric instruments.